Medical Student Balint – a Tool to Improve Empathy, Transform Communication Skills and Empower Tomorrow’s Socially Aware Patients’ Advocates - Justyna Wroblewska; Burak Cardak; Michael Milmore (BJPsych Open, 2025)
Aims: A trial of Balint Group for eleven medical students during their psychiatry placement in Rotherham, UK, to add to the existing pool of evidence regarding the impact of Balint Group on empathy, communication skills, understanding of doctor-patient interaction and to improve the understanding of the wider socio-political context of patients, with the hope of developing agency, consultation abilities, advocacy and well-being among future doctors.